Humanization in Health: Integrating the Human-Centered Approach in Hospital Management to Improve Quality of Care - E. , Urete Barrera, Mery; lopez, John Danilo pedraza; Munévar, Derly Caterine Rodríguez (Journal of Posthumanism, 2024)
Objective. To analyze the impact of the human-centered design approach in humanized medical care. Methods. A literature review was conducted using the Scopus and Web of Science databases. A search equation was used that included key terms delimited by Boolean operators, such as (humani?ation OR "human centered" OR "design thinking") AND ("health care" OR "health services") AND (model OR policy OR project) AND NOT ("Artificial Intelligence" OR robot* OR covid). Results. Twenty open access type articles published in the last 5 years in relevant areas such as nursing, human and social sciences, applying human-centered design or design thinking to improve health care were selected. Articles related to digital transformation or virtual reality were excluded, and the main objective was to improve humanizing practices in health care. Conclusion. The literature review demonstrates that the human-centered design approach has a significant impact on the promotion of humanized health care, improving practices and the quality of health services by considering the patient as the center of the care process.